Business Training: lecture summary - Mokhniuk, Anna; Shostak, Liudmyla; Pavlov, Kostiantyn (My University, 2023)
The discipline “Business Training” belongs to the elective disciplines and is aimed at mastering knowledge of the functioning and effective management of businesses in modern economy. The plan of the discipline involves various topics such as: features of business organization, opportunities for benchmarking, outsourcing and other models, adaptation of modern methods of staff motivation at Ukrainian enterprises, basic approaches to assessing the effectiveness of advertising, methods of strategic analysis and more.
Lecture summary of the discipline “Business training” is designed to develop students’ entrepreneur skills. Masters will learn how to make effective management decisions in the globalised environment as well improve English. Recommended for training masters of the branch of knowledge 07 “Management and administration” in specialty 076 "Entrepreneurship, trade and exchange activities".
Keywords: Business Training; 330.33 (072)